2018
DOI: 10.1002/ijgo.12542
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Opportunity‐Ability‐Motivation behavior change framework into a coaching‐based WHO Safe Childbirth Checklist program in India

Abstract: ObjectiveTo evaluate whether integration of the Opportunity‐Ability‐Motivation plus Supplies (OAMS) framework into coaching improved the delivery of essential birth practices in a low‐resource setting.MethodsThis prospective mixed‐methods study used routine coaching visit data obtained from the first eight intervention facilities of the BetterBirth trial in Uttar Pradesh, India, between December 19, 2014, and October 21, 2015. The 8‐month intervention was peer coaching that integrated the OAMS framework to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In this study, all facilities were primary-level health facilities located in Uttar Pradesh, and all coaching was provided by external peer coaches according to the opportunity-ability-motivationssupplies framework. 33 Consequently, we do not know the extent to which the relationships observed in this analysis can be generalized to other settings or to other forms of coaching. Contextual factors, including staffing levels, facility infrastructure, and the interactions between coaching activities and traditional supervision processes may modify the effectiveness of coaching.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In this study, all facilities were primary-level health facilities located in Uttar Pradesh, and all coaching was provided by external peer coaches according to the opportunity-ability-motivationssupplies framework. 33 Consequently, we do not know the extent to which the relationships observed in this analysis can be generalized to other settings or to other forms of coaching. Contextual factors, including staffing levels, facility infrastructure, and the interactions between coaching activities and traditional supervision processes may modify the effectiveness of coaching.…”
Section: Discussionmentioning
confidence: 95%
“…The BetterBirth Program used an engagelaunch-support model, which has been previously described in detail. [32][33][34] Briefly, district-and facilitylevel leadership were introduced to the BetterBirth program and engaged to identify priority areas for improvement related to the SCC. Each facility held an educational and motivational launch event to train birth attendants on using the SCC.…”
Section: Box Coaching Intensity Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, supply stockouts pose a significant barrier to delivery of high quality maternal and neonatal care. During the BetterBirth trial, supplies were observed as an obstacle to providing care in 10% of coaching sessions (Hirschhorn et al 2018).…”
Section: Introductionmentioning
confidence: 99%